Quality of Slaughtered Pork on Stunning with Captive Bolt and Without Stunning Review of Water Holding Capacity, Wetted Area and Cooking Loss - Adnyani, Ni Made Rita (Journal of Veterinary and Animal Sciences; Vol 5 No 2 (2022)DO - 10.24843/JVAS.2022.v05.i02.p03, 2022)
Pigs are livestock that have great potential in the economic field, judging from the level of pork consumption in Bali, which is in great demand and has always been a superior commodity among the public. The purpose of this study was to determine the quality of pork slaughtered at the grounding using a captive bolt and non stunning which was reviewed from the parameters of water holding capacity, wetted area and cooking loss. This study used 40 samples of pork on the hamstrings (musculus biceps femoris), weighing 50 gr/head taken from two different slaughterhouses in the Darmasaba area. The results showed that the value of water holding capacity and wet area of   meat without stunning and with captive bolt stunning showed no difference, while the cooking loss of meat without stunning and with stunning had differences. Further research needs to be done on the right method that can reduce the movement of animals when slaughtered to make it easier for butchers.